Prostate cancer imaging image analysis and image-guided interventions : international workshop, held in conjunction with MICCAI 2011, Toronto, Canada, September 22, 2011 : proceedings - Madabhushi, Anant (Lecture notes in computer science, 2011)
This book constitutes the refereed proceedings of the International Workshop on Prostate Cancer Imaging, held in conjunction with MICCAI 2011, in Toronto, Canada, in September 2011. The 15 revised full papers presented together with 2 invited talks were carefully reviewed and selected from 19 submissions. The papers cover the clinical areas of radiology, radiation oncology, and image guided intervention, addressing topics such as prostate segmentation, multi-modal prostate registration, and computer-aided diagnosis and classification of prostate cancer.